Eco‐driving control for hybrid electric trams on a signalised route. Issue 1 (5th December 2019) - Xiao, Zhuang; Feng, Xiaoyun; Wang, Qingyuan; Sun, Pengfei
Abstract : This study proposes an integrated eco‐driving controller, in which speed profile and power split optimisation are simultaneously treated. A speed profile controller is designed based on a multi‐phase dynamic programming (DP) algorithm, which is utilised to optimise speed trajectories with the detailed model of the traction power system, vehicle dynamics system, and signal constraints at intersections. The optimised speed and demand power profiles are designed as the reference of the power split optimal controller. A DP algorithm is presented to determine voltage trajectories of supercapacitors with power plant voltage limitations and dynamic power losses. The performance of the proposed integrated method is evaluated by numerical simulation based on an actual route of Chengdu Tramway Line 2. The energy reduction can be achieved by the speed profiles controller, compared to the eco‐cruising benchmark strategies. Energy efficiency can be further improved by the integrated eco‐driving controller. Moreover, the influences of green signal time windows and trip time on the shape of the optimised solution are investigated. For a given journey, the trip time with minimum energy consumption can be obtained. The integrated eco‐driving control method can be implemented by driver assistant systems or automatic train operation systems.